Study on the Calculation Method of Molten Pool Decay Heat Distribution under IVR Condition - Hao, Yisheng; Chen, Junyi; Luo, Hao; Guo, Xiaoyu; Liu, Minyun; Huang, Shanfang; Wang, Kan; Gong, Houjun; Li, Yang; Hu, Yuwen; Lu, Chuan (Frontiers in Energy Research, 2021)
As an important strategy to mitigate severe accidents, the in-vessel retention (IVR) technique has been applied to the new generation of pressurized water reactor (PWR). However, under IVR conditions, the decay heat distribution in the molten pool is very uncertain because of the complexity of the molten pool and the calculation method limitations. To explore the calculation method and distribution of the decay heat of lower head molten pool under IVR conditions, the decay heat calculation method is developed based on Reactor Monte Carlo Code (RMC). The verification results show that the relative error of calculation result is generally within ± 0.25%. In addition, geometric modeling for lower head molten pools has been carried out, and distribution of the decay heat in two-layer and three-layer structures has also been accurately calculated. The calculation results indicate that the decay heat power spatial distribution is relatively uniform in the two-layer molten pool structure. The decay heat power at the center of the lower head decreases from 0.71°W/cm3 to 0.023°W/cm3 within 1d-5d. In the three-layer molten pool structure, the spatial distribution of the decay heat power is severely uneven due to the precipitation of heavy metal uranium. Besides, in actual engineering calculations, it should lay emphasis on the heat transfer characteristics and design margin of the upper part of the heavy metal layer and the lower part of the oxide layer because the maximum decay heat power appears at these two positions.